PENGARUH KOMPRES HANGAT TERHADAP NYERI PADA PENDERITA HIPERTENSI - Tantri Puspita; Sri Yekti Widadi; Rudy Alfiansyah; Eldessa Vava Rilla; Wahyudin Wahyudin; Dian Octavia; Selvi Estria (Asosiasi Dosen Muda Indonesia, 2023)
Hypertension is commonly a problem because of the blood pressure are above the normal. Signs of symptoms felt by patients with hypertension are headache, dizziness, weakness, fatigue, shortness of breath, nausea and vomiting, pain in the neck. A warm compress on the neck is one of the non-pharmacological ways to reduce or eliminate neck pain. Patients with hypertension will feel a warm or hot sensation in the nape area after applying warm compresses. This study was to determine whether warm compresses influence reducing blood pressure in hypertensive patients. This research was conducted in Kp Kostarea 2 RT 02 RW 03 Mekarluyu Village, Sukawening District, Garut, West Java. This study used a pre-experimental design with the type of one-group pretest-posttest design (one group pretest-posttest). A total of 15 respondents were involved in the study which were taken by purposive sampling. The result showed that most of the respondents were female amount 11 (73.3%). Overall respondents experienced a decrease in pain scale and systolic and or diastolic blood pressure. The results of the Wilcoxon test showed that there was an effect of using warm compresses on reducing the pain scale of patients with hypertension Asymp.Sig. (2-tailed) = 0.000 <0.05. Warm compresses can be used as independent therapy for nurses in patients with neck pain with hypertension.